Pengertian, Penerapan serta Dasar Hukum Akutansi Jasa Kafalah - Islamiyanti, Irda; Umasugi, Nirwan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to find out the meaning, application and legal basis of Kafalah accounting through existing literary sources. The research method used in this paper uses a literature review method, where the researcher will collect studies related to this journal. Kafalah is a guarantee given by the guarantor (kafil) to a third party to fulfill the obligations of the second party or the insured. Kafalah can be called a guarantee. A contract means a bond made by two or more people, between individuals and/or groups, in which there is a bond of agreement that gives rise to obligations for each party according to Islamic principles. A guarantor with the approval of a third party for the benefit of a debtor, by binding himself if the debtor does not comply. The basis of the kafalah contract contains general provisions which contain a statement that the ijab qabul must be stated by the parties to show their will to carry out the contract (contract), the guarantor can receive compensation (fee) as long as it is not burdensome, the kafalah is binding and cannot be cancelled unilaterally